2022
DOI: 10.1101/2022.03.04.482790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ReLo is a simple and quick colocalization assay to identify and characterize direct protein-protein interactions

Abstract: Characterizing protein-protein interactions (PPIs) is fundamental for understanding biochemical processes. Many methods have been established to identify and study direct PPIs; however, screening and investigating PPIs involving large and poorly soluble proteins remain challenges. As a result, we developed ReLo, a simple cell culture-based method to detect and investigate interactions in a cellular context. ReLo allows both the identification of protein domains that mediate the formation of complexes and scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 89 publications
2
26
0
Order By: Relevance
“…Therefore, to assess protein interactions to Short Oskar, it carried an N-terminal fusion to OST4, a small membrane protein that directed Short Oskar localization to the endoplasmic reticulum (ER). Using OST4-anchored Short Oskar, we have previously confirmed the known direct interaction with the DEAD-box RNA helicase Vasa (Supplemental Figure 7A) (Salgania et al, 2022;Jeske et al, 2017Jeske et al, , 2015. Here, we show that OST4-Short Oskar interacted also with Smaug (Figure 4B), which is consistent with earlier observations (Dahanukar et al, 1999;Jeske et al, 2011;Zaessinger et al, 2006).…”
Section: Oskar Directly Binds To Smaugsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, to assess protein interactions to Short Oskar, it carried an N-terminal fusion to OST4, a small membrane protein that directed Short Oskar localization to the endoplasmic reticulum (ER). Using OST4-anchored Short Oskar, we have previously confirmed the known direct interaction with the DEAD-box RNA helicase Vasa (Supplemental Figure 7A) (Salgania et al, 2022;Jeske et al, 2017Jeske et al, , 2015. Here, we show that OST4-Short Oskar interacted also with Smaug (Figure 4B), which is consistent with earlier observations (Dahanukar et al, 1999;Jeske et al, 2011;Zaessinger et al, 2006).…”
Section: Oskar Directly Binds To Smaugsupporting
confidence: 91%
“…To analyze protein interactions between proteins, we have recently developed ReLo, a cell culture-based protein-protein interaction assay that is based on a subcellular translocation readout (Salgania et al , 2022). Our previous analyses strongly suggested that interactions identified with the ReLo assay are direct (Salgania et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between Smaug and individual CCR4-NOT subunits present in the MINI complex were examined by a recently described in vivo interaction assay based on intracellular protein relocalization (ReLo assay) (Salgania et al, 2022). For this assay, CCR4-NOT subunits were fused with mCherry and with the pleckstrin homology (PH) domain of rat phospholipase Cd1 and expressed as bait in Drosophila S2R+ cells; the PH domain caused their localization on the plasma membrane.…”
Section: Smaug Interacts With the Not Modulementioning
confidence: 99%
“…ReLo assays were performed as described (Salgania et al, 2022). In short, Drosophila S2R+ cells were seeded onto four-well chambered coverslips (Ibidi), co-transfected with the desired combination of pAc5.1 plasmids expressing the two proteins of interest, and protein localization was analyzed after two days by live confocal fluorescence microscopy.…”
Section: Protein-protein Interaction Assaysmentioning
confidence: 99%